Organizational Justices and Employees' Demography: Empirical Evidence form Nepalese Employees - Bhattarai, Ganesh (Researcher: A Research Journal of Culture and Society, 2020)
In the context of controversial empirical evidences regarding the effect of demographic variables on organizational justices, this study was carried out to measure the (a) employees' perceived organizational justice within the different demographic groups, and (b) the impact of demographic aspects (i.e., sex, tenure, and education) on organizational justices. Five hundred forty-six employees working in Nepalese commercial banks were taken as the sample. Perceptual cross-sectional data were analyzed quantitatively using both descriptive and inferential statistics. This study revealed that the average level of perceived justices was more than fifty percentages on five-point Likert-type scales, indicating they did not feel injustice. Females than males, temporary than permanent, and master's degree holders than bachelor's degree holders perceive less distributive justice. Likewise, female than male, permanent than temporary, master's degree holders than higher or lesser degree holders perceive less procedural justice. Similarly, regarding interactive justice, male than female, temporary than permanent, and master's degree holders than bachelor's degree holders feel comparatively less honesty, courtesy, respect, and politeness in their working relationship. Some empirical and theoretical implications are suggested.